(3QSGdI aj Yde GdESWQdGHs - (3Ydj Hf YjSis ((3eOjfI GdCScfOQjI s)
(3ChdgG (B:s
(3GdMeO ddg hMOg eYQaI fXQ GdJKdjK hGdJSOjS hGdebGHdI (B( (3Ke JfJgi gPg GdUaMI hJHOC GdJGdjI dgG HGdHSedI Ke (B( (3GdHGH GdChd ajeG jMJGL Edjg ef Yde GdESWQdGH (B) s
(3BNQgG (B:s
(3agPG gh GdhLg ai Pdc Ef TGA Gddg JYGdi , hGdMeO ddg QH GdYGdejf cedJ GdQSGdI s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(976/3) s
Keywords: (3Gdadcs